The Microbiome: A Life Science Opportunity for Our Society and Our Planet. Issue 12 (December 2019) - Małyska, Aleksandra; Markakis, Marios Nektarios; Pereira, Carina F.; Cornelissen, Marc
Abstract : Microbiome research and innovation (R&I) promises solutions to a broad range of business and societal challenges. To bridge the gap between today's potential and the moment at which concrete applications start generating societal impact, critical-scale efforts offering visible progress on topics of public interest will be essential.